PENGARUH PROFITABILITAS DAN INTENSITAS MODAL PADA PENGHINDARAN PAJAK DENGAN UKURAN PERUSAHAAN SEBAGAI VARIABEL MODERASI - Tri Paramita, Komang; Rasmini, Ni Ketut (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.13.NO.09.TAHUN.2024, 2024)
The purpose of this study was to examine the effect of profitability and capital intensity on tax avoidance with firm size as a moderating variabel. This research was conducted at energy sector companies listed on the Indonesia Stock Exchange in 2019-2021. The number of sampels used in this study were 21 companies with a total of 63 observations obtained by purposive sampling method. The data analysis technique used in this study is the Moderated Regression Analysis (MRA) technique. The results showed that profitability has a negative effect on tax evasion. Capital intensity has a positive effect on tax avoidance. Firm size strengthens the effect of profitability on tax avoidance. Firm size weakens the effect of capital intensity on tax avoidance.